Genetic and epigenetic alterations in night shift nurses with breast cancer: a narrative review - Xia Li; Yingyu Hu; Fatemeh Aslanbeigi (Cancer Cell International)
Abstract This narrative review explores the link between breast cancer and night shift work in nurses, focusing on genetic and epigenetic factors. Breast cancer disproportionately affects women globally, and night shift work is increasingly recognized as a potential risk factor. Nurses who work consecutive overnight shifts face elevated risks due to disruptions in their circadian rhythms. Studies suggest that working six or more successive night shifts, particularly over five years or more, may increase breast cancer risk. This review hypothesizes that disruptions in the sleep-wake cycle, such as changes in melatonin production and telomere length, could contribute to breast cancer susceptibility. Currently, there is limited genetic evidence to support this hypothesis. However, it is plausible that genetic and epigenetic alterations, including changes in genes like ER and HER2, may heighten the risk for night shift nurses. These alterations may involve variations in telomere length, DNA methylation, and disruptions in critical breast cancer-related genes. We highlight various genetic and epigenetic changes that may influence this increased susceptibility. Further research is needed to explore the underlying mechanisms and contributing factors in this association.